Using the Edge Detector for Face Recognition Based on Eigenedge FacesMethod - Hameed, Hussein (Iraqi Journal of Science, 2024)
In this paper is designed a system capable to recognize and distinguish a humanface on the others are located within the database, depending on the methodof eigenedge faces, after the effect edge detection (Sobel operator), the systemis running by the language of MATLAB. The comparison has been completebetween the test image and the group of different images by criterion MinimumMean distance.Power system has been test on one of the problems can occur between the testimage and the camera, in terms of the shift image (to the right, left, upand down) from the camera.